2017
DOI: 10.1371/journal.pgen.1006629
|View full text |Cite
|
Sign up to set email alerts
|

The Legionella pneumophila genome evolved to accommodate multiple regulatory mechanisms controlled by the CsrA-system

Abstract: The carbon storage regulator protein CsrA regulates cellular processes post-transcriptionally by binding to target-RNAs altering translation efficiency and/or their stability. Here we identified and analyzed the direct targets of CsrA in the human pathogen Legionella pneumophila. Genome wide transcriptome, proteome and RNA co-immunoprecipitation followed by deep sequencing of a wild type and a csrA mutant strain identified 479 RNAs with potential CsrA interaction sites located in the untranslated and/or coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 84 publications
7
87
0
1
Order By: Relevance
“…Recent findings from transcriptomics studies have led to the discovery that CsrA binding occurs at the 3′ UTR of a few transcripts, but occurs predominantly deep within the coding regions of mRNAs (29, 31, 34, 35). Furthermore, CsrA binding within mRNA coding regions is significantly increased in frequency near ribosome pause sites (35).…”
Section: Rna-mediated Csra Antagonismmentioning
confidence: 99%
“…Recent findings from transcriptomics studies have led to the discovery that CsrA binding occurs at the 3′ UTR of a few transcripts, but occurs predominantly deep within the coding regions of mRNAs (29, 31, 34, 35). Furthermore, CsrA binding within mRNA coding regions is significantly increased in frequency near ribosome pause sites (35).…”
Section: Rna-mediated Csra Antagonismmentioning
confidence: 99%
“…In the post-exponential growth phase L. pneumophila induces (de-represses) transmissive traits such as virulence, motility and stress resistance. The phase switch is controlled by a complex regulatory network, including the twocomponent system LetAS (Segal, 2013), the RNA-binding global regulator CsrA (carbon storage regulator A) (Sahr et al, 2017) and the Lqs system ( Fig. 1A) (Hochstrasser and Hilbi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous L. pneumophila EEGs have been shown before to be directly regulated by the PmrAB TCS (Zusman et al, ; Al‐Khodor et al, ) and by the LetAS‐RsmYZ‐CsrA regulatory cascade (Rasis and Segal, ; Nevo et al, ; Sahr et al, ). However, no EEGs (or any other genes) which are regulated by both of these regulatory systems were previously described.…”
Section: Resultsmentioning
confidence: 99%
“…These four TCSs are responsible for the regulation of more than 100 L. pneumophila effector-encoding genes (EEGs) (Segal, 2013). These TCSs consist of (i) the PmrAB TCS, which includes the PmrA response regulator (RR) and the PmrB sensor histidine kinase (SHK), that was shown to directly activate the expression of 42 EEGs (Zusman et al, 2007;Al-Khodor et al, 2009;Speiser et al, 2017); (ii) the CpxRA TCS, which includes the CpxR RR and the CpxA SHK, that was shown to directly activate or repress the expression of 27 EEGs and four Icm/Dot components (Gal-Mor and Segal, 2003a;Feldman and Segal, 2007;Altman and Segal, 2008;Feldheim et al, 2016;Tanner et al, 2016); (iii) the LetAS TCS, which includes the LetA RR and the LetS SHK (Hammer et al, 2002;Gal-Mor and Segal, 2003b), that was shown to activate the transcription of two small regulatory RNAs (RsmY and RsmZ) during stationary phase (Hovel-Miner et al, 2009;Rasis and Segal, 2009;Sahr et al, 2009), which act in a redundant fashion to jointly antagonize CsrA, an RNA-binding protein that negatively regulates the expression of about 40 EEGs at the translational level (Nevo et al, 2014;Sahr et al, 2017); (vi) the LqsRS TCS and its signaling molecule LAI-1, which were also shown to affect the expression of EEGs, but since LqsR lacks a DNA binding domain, the way by which this regulation is mediated is currently not known (Tiaden et al, 2007;Schell et al, 2014;2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation